PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI PERMAINAN TANTANGAN (CHALLENGE PLAY) PADA ANAK DI TAMAN KANAK-KANAK - Eliza Puspa Dewi; Nurhafizah, Nurhafizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve children's gross motor skills through challenging games in Restu Ibu Kindergarten in Koto Jorong III Maek, Bukik Barisan District, Lima Puluh Kota Regency, West Sumatra Province. This study is a classroom action research conducted in 2 cycles. The subjects in this study were 13 children in group B consisting of 7 boys and 6 girls. Data collection techniques were carried out by observation, while data analysis used statistical formulas for average and percentage tests. Before the study, the average ability of children was only around 20% of children who had begun to develop gross motor skills, after the first cycle of research, children's gross motor skills were at around 38.5% of children who were in the Developing as expected category because the results of the study had not reached the minimum results of completeness, then the second cycle was carried out, the children's completeness was at 78% of children who were already in the Developing as Expected category and some children were in Very Good Development, so the study stopped in the second cycle and the study was considered successful because it was considered effective in developing children's fine motor skills. Keywords: Gross motor skills, early childhood, Classroom Action Research, challenge games, physical development.